Use of 3d model in the study of tower crane stability - Ivanenko, О. I.; Musaiev, Z. R. (ХНУРЕ, 2025)
The article presents the results of a study of the stability of a tower crane during operation, taking into account the influence of loads on the supports. The results of comparing the distribution of loads on the crane supports determined as a result of mathematical and computer modeling during the turning and lifting of the boom are presented. An analysis of tower crane designs, installation methods and operating conditions, as well as methods for calculating their stability, shows that recently there has been a need to install cranes that can handle loading and unloading operations in confined spaces. This raises the question of how important the stability of cranes under different operating conditions and different wind loads is. In this case, the correct choice of the support circuit comes to the fore, for which it is very important to determine the loads on the support elements. У статті представлено результати дослідження стійкості баштового крану під час експлуатації з урахуванням впливу навантажень на опори. Наведено результати порівняння розподілу навантажень на опори крану, визначених у результаті математичного та комп’ютерного моделювання під час повороту та підйому стріли. Аналіз конструкцій баштових кранів, методів їх монтажу та умов експлуатації, а також методів розрахунку їх стійкості показує, що останнім часом зросла потреба у встановленні кранів, здатних виконувати вантажно-розвантажувальні роботи в обмежених просторах. Це питання про важливість забезпечення стійкості кранів в умовах різної експлуатації та дії вітрових навантажень. У такому випадку на перший план виходить правильний вибір опорного контуру, для чого надзвичайно важливим є визначення навантажень на опорні елементи.
Keywords: research; tower crane; stability; load distribution; computer model; комп’ютерна модель; комп’ютерна модель; адекватність